EMERGENCY SMS SERVICES FOR DISABLED PATIENTS - Aditya Nugraha (Universitas Gunadarma, 2017)
Many learning method to educate children with special needs, such as learning to use the application through iPad, or use other special tools. In the learning phase that usually they are accompanied by a parent/baby sitter. The parents or babysitters not always 24 hours at their side. Could be because parents who go to work, or when the babysitter left the children while sleeping. When left as it is, if the children need help suddenly it will be difficult to recall the parent/babysitter page. To overcome this,there is an idea to make a communication tools using short message service media and using Arduino platform. The tool is specifically designed for patients/children with special needs so it is easy to operate and can quickly contact their parents.Theresults of the design tool is a tool is capable of sending SMS with a delay 5 seconds from the button is pressed and have outreach as far as 14,5 meters from GSM modem. Keywords: GSM modem, Message alert, Arduino, RF remote control, frequency